2015
DOI: 10.1007/s00234-015-1517-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between idiopathic intracranial hypertension and sigmoid sinus dehiscence/diverticulum with pulsatile tinnitus: a retrospective imaging study

Abstract: Several IIH imaging features occur more frequently in PT patients with SSDD than in healthy individuals, which suggests a potential correlation between SSDD with PT and IIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…More recently, sigmoid sinus diverticulum and/or dehiscence (SSDD) has been shown to be associated with PT. 1,[11][12][13][14][15][16] This association has been noted to be particularly frequent in patients with elevated body mass indices and those with imaging features of IIH, 1,14,15 leading some authors to suggest that SSDD may reflect a manifestation of subclinical IIH. 2,14 Interventional studies have revealed that endovascular stenting of TSS or surgical correction of SSDD may resolve PT 5,7,8,13,[17][18][19] ; however, these procedures are not without complications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, sigmoid sinus diverticulum and/or dehiscence (SSDD) has been shown to be associated with PT. 1,[11][12][13][14][15][16] This association has been noted to be particularly frequent in patients with elevated body mass indices and those with imaging features of IIH, 1,14,15 leading some authors to suggest that SSDD may reflect a manifestation of subclinical IIH. 2,14 Interventional studies have revealed that endovascular stenting of TSS or surgical correction of SSDD may resolve PT 5,7,8,13,[17][18][19] ; however, these procedures are not without complications.…”
Section: Resultsmentioning
confidence: 99%
“…28 Patients with PT and SSDD have been found to have clinical and imaging characteristics of IIH. 1,12,15 A number of mechanisms have been proposed to explain this association. It is possible that the impact of pulsatile, turbulent blood flow on the sinus wall could cause the formation of SSDD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSWD is likely to occur during pneumatization of the mastoid in older adolescence or the early adult years. And PT may arise when blood flow turbulence occurs, which can be generated by the increased irregularity of the vessel diameter or ipsilateral dominance of the drainage system [14, 31, 32]. Mechanical compression of the sigmoid sinus is an efficient method to correct the blood flow turbulence and cure PT [21, 25]; however, it may cause increased intracranial pressure following surgery if extensive compression is performed [26].…”
Section: Discussionmentioning
confidence: 99%
“…This demographic feature resembles that of patients with idiopathic intracranial hypertension (IIH). Furthermore, several IIH imaging features occur more frequently in PT patients with SSD and/or SSWD than in non-PT individuals [32], indicating that IIH may be an underlying cause in some PT patients with sigmoid sinus anomalies. Possible reasons for this could be that the elevated intracranial pressure gradually erodes the osseous wall of the sigmoid sinus, resulting in wall dehiscence and diverticulum, or that the elevated intracranial pressure causes blood flow turbulence and leads to PT.…”
Section: Discussionmentioning
confidence: 99%